Association of the leukemia inhibitory factor gene polymorphism rs929271 with idiopathic mild intellectual disability - Gulkovskyi, R.V.; Volkova, L.S.; Livshits, L.A. (2015)
Aim. To investigate the possible association of LIF gene polymorphism rs929271 with mild intellectual disability (ID). Methods. The group of patients with mild (IQ score between 50 and 70) idiopathic intellectual disability consisted of 64 individuals including 40 (62.5 %) males and 24 (47.5 %) females. The control group consisted of 238 healthy volunteers from different regions of Ukraine. Polymorphic variants of LIF gene rs929271 were detected using PCR followed by Hinf1 RFLP analysis. Results. The data concerning LIF genotypes and allelic variants distribution in ID patients and control group were obtained. Statistical analysis shows significant differences at rs929271 for both genotype and allele frequency when comparing ID cases and controls (p = 0.01 and 0.02, respectively). Conclusions. Our results suggest that LIF gene polymorphism rs929271 is associated with idiopathic mild intellectual disability. Therefore, we propose LIF as a new marker of genetic susceptibility for intellectual disability. Мета. Дослідити можливу асоціацію поліморфізму rs929271 гена LIF з легкою інтелектуальною недієздатністю (ІН). Методи. Група пацієнтів з легкою (IQ між 50 і 70) ідіопатичною інтелектуальною недієздатністю складалася з 64 індивідів, включаючи 40 (62,5 %) чоловіків і 24 (47,5 %) жінки. Контрольна група складалася з 238 здорових добровольців з різних регіонів України. Поліморфні варіанти rs929271 гена LIF виявляли за допомогою ПЛР з подальшим Hinf1 ПДРФ аналізом. Результати. Були отримані дані про розподіл генотипів і алельних варіантів гена LIF в групі пацієнтів з ІН і в контрольній групі. Статистичний аналіз показує значимі відмінності по rs929271 як для частот генотипів, так і алельних варіантів при порівнянні досліджуваної та контрольної груп (р = 0,01 і 0,02, відповідно). Висновки. Наші результати показують, що поліморфізм rs929271гена LIF асоційований з легкою ідіопатичною інтелектуальною недієздатністю. Тому ми пропонуємо LIF в якості нового маркера генетичної схильності до інтелектуальної недієздатності. Цель. Исследовать возможную ассоциацию полиморфизма rs929271 гена LIF с легкой интеллектуальной недееспособностью (ИН). Методы. Группа пациентов с легкой (IQ между 50 и 70) идиопатической интеллектуальной недееспособностью состояла из 64 индивидов, включая 40 (62,5 %) мужчин и 24 (47,5 %) женщины. Контрольная группа состояла из 238 здоровых добровольцев из разных регионов Украины. Полиморфные варианты rs929271 гена LIF выявляли посредством ПЦР с последующим Hinf1 ПДРФ анализом. Результаты. Были получены данные о распределении генотипов и аллельных вариантов гена LIF в группе пациентов с ИН и в контрольной группе. Статистический анализ показывает значимые различия по rs929271 как для частот генотипов, так и аллелей при сравнении исследуемой и контрольной групп (р = 0,01 и 0,02, соответственно). Выводы. Наши результаты показывают, что полиморфизм rs929271гена LIF ассоциирован с легкой идиопатической интеллектуальной недееспособностью. Поэтому мы предлагаем LIF в качестве нового маркера генетической предрасположенности к интеллектуальной недееспособности.